IWork '09 for dummies - Feiler, Jesse (--For dummies., 2009)
"Be productive the Mac® way! Discover the creative possibilities of iWork '09. Not only can you do the same things with iWork that you can with that "other" suite of office productivity tools, but you can spend less and be more creative too. Here's how to start creating slick-looking documents and page layouts with Pages, knockout charts and reports with numbers, and presentations with polish using Keynote. Why settle for less?"--Publisher's description